A review of glycoconjugate vaccines: The current state of the technology, considerations for the future, and the gold standard carrier protein, CRM(197) - Meeds, Oliver (2023)
Part A: Conjugation of bacterial capsular polysaccharides to immunogenic carrier proteins has been employed for almost five decades to protect infants and adults against bacterial infections. This review investigates the immune mechanisms, conjugation chemistry, and carrier protein interactions that define glycoconjugate technology, and reports on the recent developments that have facilitated a renewed interest into the field of conjugated vaccines. With novel methodologies such as bioconjugation and Generalized Modules for Membrane Antigens (GMMA) reaching maturity, and the carrier protein CRM(197) seeing a research-renaissance, molecular characterization has never been more important. Elucidation of the physiochemical properties of prospective therapeutics is a crucial quality control measure that allows their structural integrity, stability, and immunogenicity to be verified. Thus, a special mention is made to the hydrodynamic methods that ensure current and novel therapeutics remain safe and efficacious.